A Study of the Market Reaction to CEO Change & CEO Gender Change for Companies Listed on the Iraq Stock Exchange (Journal of Accounting and Financial Studies ( JAFS ), 2024)
Abstract :           The current study aims to determine how the market will respond to changing the managing director's sex and how this move will impact the anomalous returns of companies. 35 companies were chosen for the period from (2010) to (2021) based on information published by companies registered on the Iraq Stock Exchange. The study's findings showed that there is a substantial inverse (negative) association between aberrant stock returns and managing director changes. The value of stock prices is diminished by investors when executive directors are replaced, which causes stock returns to be less than anticipated. I also found that there is no significant relationship between the gender of the managing director and abnormal stock returns